Body mass index and glioma risk: A prospective multicenter study - Shao, Chuan; Tang, Hui; Wang, Xiaoya; He, Jiaquan; Wang, Pan; Wu, Nan (Frontiers in Endocrinology, 2022)
Background The association between glioma risk and body mass index (BMI) remains obscure. Methods This study aimed to assess the association between glioma risk and BMI in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. Cox proportional hazard regression was used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs). Results The onset of a total of 269 gliomas was observed during a median follow-up period of 12.04 years. Compared with the normal weight, overweight (HR: 1.05, 95% CI: 0.80, 1.39) and obesity (HR: 0.91, 95% CI: 0.56, 1.39) were not significantly associated with glioma risk. Further analysis showed a nonlinear relationship between glioma risk and BMI in men but not women. The multivariable-adjusted HRs per unit increase in BMI were 0.94 (95% CI: 0.89, 1.00, P=0.037) in men with BMI >25 kg/m2 and 1.16 (95% CI: 0.98, 1.38, P=0.075) in men with BMI <25 kg/m2. Conclusion The present data provide evidence that there may be a nonlinear association between BMI and glioma risk in men. The risk of glioma decreased with increasing BMI among men with BMI >25 kg/m2. Future studies are needed to validate our observation.